Uji Keberagaman Umur Batang Bawah Kakao (Theobroma Cacao L.) Pada Teknik Sambung Pucuk - Rizky, Muhammad Nazli; Siregar, Tumpal HS (Universitas Medan Area, 2025)
Cocoa (Theobroma cacao L.) is a strategic commodity in the plantation subsector that plays an important role in the Indonesian economy, both as an industrial raw material and a source of foreign exchange for the country. However, cocoa productivity at the farmer level is still relatively low, one of which is due to the use of genetically non-uniform generative seeds. To overcome this problem, the vegetative propagation technique through shoot grafting is an effective alternative because it is able to maintain the superior properties of the mother plant and accelerate the fruiting period. This study aims to examine the optimal lifespan of the rootstock in the cocoa shoot grafting technique through a literature study approach. The analysis was carried out on 22 scientific articles published in 2012–2023 that met the criteria of relevance, scientific reputation, and focus on cocoa plant propagation. The results of the study show that the lifespan of the rootstock between 8–10 weeks is the most optimal phase for splicing, because at that age the stem tissue has an ideal balance between flexibility and physiological maturity. Other factors such as upper and lower stem compatibility, joining techniques, and environmental conditions also greatly affect the success rate. This study provides a practical basis for the efficient and sustainable development of cocoa nurseries.